Smoking, consumption of alcohol and sedentary life style in population grouping and their relationships with lipemic disorders - Ignez Salas Martins; Leda Teixeira Coelho; Monica Inés Casajus; Elisa Tieko Okani (Universidade de São Paulo, 1995)
The study, part of the project "Atherosclerotic cardiovascular diseases, lipemic disorders, hypertension, obesity and diabetis mellitus in a population of the metropolitan area of the southeastern region of Brazil", had the following objectives: a) the characterization and distribution among typical human socio-economic groupings, of the prevalence of some particular habits which constitute aspects of life-style-the use of tobacco, the use of alcohol and sedentary activity; b) the establishment of the interrelation between the above-mentioned habits and some lipemic disorders. The prevalence of the habits cited behaved in the following manner: the use of tobacco predominated among men, distributed uniformly throughout the social strata; among the women the average percentage of smokers was 18,9%, a significant difference occurring among the highest socio-economic class, where the average was of 40.2%. The sedentary style of life presented high prevalence, among both men and women with exception of the women of the highest socio-economic level and of the skilled working class. The use of alcohol, as one would expect, is a habit basically practised by the men, without any statistically significant differences between classes. For the purpose of establishing associations between these risk fictors and lipemic conditions four situations were chosen, of the following characteristics: 1- total cholesterol > or = 220 mg/dl and triglycerides > or = 150 mg/dl; 2- HDL cholesterol <35 mg/dl for men and <45 mg/dl for women and triglycerides levels > or = 150 mg/dl; 3- HDL cholesterol <35 mg/dl for men and <45 mg/dl for women and triglycerides levels <150 mg/dl; 4- total cholesterol 220 mg/dl with triglycerides levels <150 mg/dl. Six models of multiple (backward) regression were established, with seven independent variables- age, sex, use of tobacco, consumption of alcohol, light physical activity, hypertension and obesity. Significant associations (P<0,05) were revealed with hypercholesterolemia, accompanied by triglyceride levels > or = 150 mg/dl, and the following independent variables: age, use of tobacco and the interactions between obesity and smoking, age and sedentary lifestyle, sex and obesity (R2=22%); the standardized B coefficient showed that the variables with the greatest weight in the forecasting of the variation in the levels of cholesterol were smoking and the interaction between obesity and smoking. The hypercholesterolemia accompanied by triglycerides levels <150 mg/dl showed a positive association between total cholesterol and sex and the interactions obesity/smoking and sex/obesity. As regards HDL cholesterol accompanied by triglyceride/ levels > or = 150 mg/dl was inversely associated with obesity and the interaction smoking/ age and directly with age (R=31%). The standardized B coeffients, indicated that the variables obesity and the interactions smoking/age possessed a weight three times greater than age alone in accounting for the variation in the serum levels of HDL cholesterol. When accompanied by triglycerides <150 mg/dl there was no association between and the independent variables and the set of them presented R equal to 22%. The sum of top, in the population stutied in this project, the component habits of life-style (smoking, alcohol consumption and sedentary activity) which constitute risk factors which determine morbidity from atherosclerotic cardiovascular diseases are be found distributed through all the typical social groupings of this particular form of social organization. On the other hand, the seven independent variables used in the multiple regression models for the explanation of the lipemic conditions considered presented multiple determination coefficients which varied, approximately, between 20% and 30%. Thus it is important that in the genetic epidemiology the study of the morbidities in question be emphasized. O estudo, parte do projeto "Doenças cardiovasculares ateroscleróticas, dislipidemias, hipertensão, obesidade e diabetes melito em população da área metropolitana da região Sudeste do Brasil", teve os seguintes objetivos: a)caracterizar a distribuição da prevalência de tabagismo, etilismo e sedentarismo entre grupamentos humanos típicos, do ponto vista socioeconômico; b)- estabelecer associações entre os hábitos e morbidades citados e determinados estados lipêmicos. A prevalência dos hábitos em questão comportou-se da seguinte forma: tabagismo, predominou entre os homens, com prevalência média de 45%, uniformemente distribuída entre as classes; entre as mulheres o percentual médio foi de 22,5%, com diferença significante para a classe de mais alto nível socioeconômico, com 46,3%. O sedentarismo apresentou alta prevalência, entre homens e mulheres, entre 40% e 50%, não havendo diferenças estatisticamente significantes entre os sexos e nem tampouco entre as classes. O etilismo foi um hábito fundamentalmente difundido entre os homens, sem diferenças de prevalência estatisticamente significantes entre as classes. Para o estabelecimento de associações entre hábitos e estados lipêmicos foram escolhidas quatro situações, com as seguintes características: 1 - Hipercolesterolemia moderada acompanhada de níveis séricos de triglicérides menores ou iguais e maiores de 150mg/dl; 2- HDL colesterol sérico abaixo da normalidade acompanhado de níveis de triglicérides iguais ou maiores de 150mg/dl ou menores de 150mg/dl. Foram estabelecidos seis modelos de regressão múltipla, com sete variáveis independentes - idade, sexo, tabagismo, etilismo, sedentarismo, hipertensão e obesidade. Na primeira situação lipêmica houve associações significantes entre a hipercolesterolemia, acompanhada de níveis de triglicérides > ou = 150mg/dl, com as seguintes variáveis independentes: idade, tabagismo e as interações entre obesidade/tabagismo, sedentarismo e sexo/obesidade, com R² igual 22%; as variáveis de maior peso na predição da variação dos níveis de colesterol total foram o tabagismo e a interação entre obesidade/tabagismo. A hipercolesterolemia acompanhada de níveis de triglicérides menores do que 150mg/dl associou-se às seguintes variáveis: sexo, interações obesidade/tabagismo e sexo/obesidade. Para a situação 2- o HDL colesterol, acompanhado de níveis de triglicérides > ou = 150mg/dl, associou-se inversamente às variáveis obesidade e a interação tabagismo/ idade e diretamente à idade (R²=31%); as variáveis obesidade e a interação tabagismo/idade apresentaram peso três vezes maior do que a idade na explicação da variação dos níveis séricos do HDL colesterol. Na presença de níveis séricos de triglicérides menores do que 150mg/dl não houve qualquer associação com as variáveis aludidas e o conjunto apresentou R² igual a 22%. Fica evidente, que as associações inversas entre HDL-colesterol com o tabagismo e obesidade, já descritas na literatura, só ocorreram na presença de níveis de triglicérides > ou = 150mg/dl. Constata-se que na presença de baixos níveis de triglicérides diminui o número de variáveis preditivas da hipercolesterolemia. Em síntese, na população abordada, os hábitos componentes do estilo de vida (tabagismo, etilismo e sedentarismo), que se constituem em fatores de risco de morbidades determinantes das doenças cardiovasculares ateroscleróticas, encontram-se distribuídos em todos os grupamentos sociais típicos nesta determinada forma de organização social. Por outro lado, as sete variáveis independentes utilizadas nos modelos de regressão múltipla apresentaram coeficientes de determinação múltipla, que variaram entre 20 e 30% aproximadamente. Ressalta-se, desta forma, a importância da epidemiologia genética no estudo das morbidades em questão.